The Effect of Storage Period and Mixing Techniques on the Chemical Content of Environmentally Friendly BIOPOS Organic Compost at SEAMEO BIOTROP - Rosita, Risa; Imran, Zulhamsyah; Fitra, Allegra Aura; Dewi, Amelia Cantrika; Bayuaji, David Yudhoyono; Dewantara Eris, Deden; Widayanti, Sri; Ayu Astari, Risya; Purnajaya, Agus (SEAMEO BIOTROP, 2024)
SEAMEO BIOTROP produces daily waste from oyster mushroom baglog (Pleurotus ostreatus), dry organic waste that contains little water, such as dry leaves, grass straw, and citronella distilled waste. Managing oyster mushroom baglog waste, leaf waste, grass straw, and citronella distilled waste independently at SEAMEO BIOTROP as organic compost BIOPOS (BIOTROP Compost) is an environmentally friendly practice and can provide benefits both economically and ecologically. Apart from being carried out to protect biodiversity from decline, this study can also keep the soil system healthy and sustainable. The aim of this research is to: (1) make BIOPOS organic compost through the use of oyster mushroom baglog, leaf waste, leaf straw, and citronella distilled waste; (2) determine the influence of various types of BIOPOS organic compost (KT1, KT2, KT3) on the chemical content of compost. Research stages include: (1) creating BIOPOS organic compost, (2) measuring the chemical content of BIOPOS organic compost, and (3) measuring the effectiveness of BIOPOS. During the storage period of 30 dam up to 180 dam, BIOPOS organic compost which still contains N (0,54%), P (36,8%), K (7,23%) and complies with SNI 19-7030-2004 quality standards is KT3. In measuring C-Organic value, BIOPOS code KT2 with a storage period of 30 dam gained C-Organic amount of 28,36%, satisfying quality standards. The application of BIOPOS KT1, KT2, and KT3 with a pH range of 8,2- 8,3 high pH can be used to correct problems that often occur in acidic soils and is not effective when applied to sub-optimal alkaline soils because it will cause soil pH to increase sharply. Key words: BIOPOS, citronella distilled waste, grass straw, leaf waste, oyster mushroom baglog waste